'Because they're a couple she should do what he says': Young People's justifications of violence: heterosexuality, gender and adulthood. Issue 3 (3rd May 2016) - Lombard, Nancy
Abstract : This article is based upon research that explored how 89 eleven- and twelve-year-olds understood and explained men's violence against women. The research found that young people examined the motivations of individual male perpetrators though the context of heterosexuality. For the young people, adulthood appeared to generate a more rigid framework of heterosexuality, where the gender differences begin to exemplify inequality upon which justifications can be based. Young people's justifications can be collated into the themes of: heteronormativity, the endorsement of marriage, restrictive gender roles and blaming women for the violence. Violence is justified because inequality is not questioned – it is endorsed and taken for granted as being part of an adult heterosexual relationship. This has implications for young people's own existing and anticipated relationships.